1990
DOI: 10.1111/j.1476-5381.1990.tb12071.x
|View full text |Cite
|
Sign up to set email alerts
|

Contractile activity of three endothelins (ET‐1, ET‐2 and ET‐3) on the human isolated bronchus

Abstract: 1 The effects of three endothelins: (i) the classical or human/porcine endothelin (ET-1); (ii) [Trp6, Leu7] endothelin (ET-2) and (iii) [Thr2, Phe4, Thr5, Tyr6, Lys7, Tyr'4] endothelin or rat endothelin (ET-3) were tested on the human isolated bronchus. 2 ET-1 produced a concentration-dependent contraction of the human isolated bronchus that proceeded in two different steps. The first step was observed at very low concentrations (pD2 = 11.01 + 0.17, n = 10) but corresponded to a low intrinsic activity (Emax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
44
1
5

Year Published

1991
1991
2002
2002

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(53 citation statements)
references
References 27 publications
3
44
1
5
Order By: Relevance
“…Acetylcholine and histamine showed a very similar contractile profile without any significant differences in Emax or pD2. The results are consistent with the results of ADVENIER et al [26] in bronchi with a diameter of 3-5 mm. The buffer solution with a high potassium concentration showed contractions which were only 53% of the acetylcholineinduced contraction.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Acetylcholine and histamine showed a very similar contractile profile without any significant differences in Emax or pD2. The results are consistent with the results of ADVENIER et al [26] in bronchi with a diameter of 3-5 mm. The buffer solution with a high potassium concentration showed contractions which were only 53% of the acetylcholineinduced contraction.…”
Section: Discussionsupporting
confidence: 83%
“…Earlier investigations have shown that ETs are potent and strong contractors of human bronchi [16,26,27]. These studies were performed on large bronchi with a diameter of 3-15 mm.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, it is possible that it is the putative ETc receptor (Martin et al, 1990;Samson et al, 1990;Masakai et al, 1992). However, this appears unlikely as this receptor exhibits selectivity for ET-3, whereas ET-1, ET-2 and ET-3 all have been shown to contract human bronchus with a rank order for potency and efficacy of: ET-l > ET-2 = ET-3 (Advenier et al, 1990;Hemsen et al, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…Its production in the vicinity of airway smooth muscle suggests that ET-1 could affect adjacent local airway tone. In vitro and in vivo studies indicate that ET-1 exerts a potent contractile effect on guinea-pig and human isolated bronchial and tracheal tissues (Uchida et al, 1988;Maggi et al, 1989;Borges et al, 1989;Advenier et al, 1990;Battistini et al, 1990). Furthermore, intravenous or aerosol administration of ET-1 to anaesthetized guinea-pigs evoked sustained bronchoconstriction (Payne & Whittle, 1988;Lagente et al, 1989;MacquinMavier et al, 1989).…”
Section: Introductionmentioning
confidence: 99%